Effects of chitosan and citric acid on pericarp browning and polyphenol oxidase activity of longan fruit - Apai W. (2014)
This research was designed to study the effects of chitosan and citric acid (CA) on pericarp browning and polyphenol oxidase (PPO) activity of longan fruit. The experiment was conducted by dipping longan fruit in 1.2% (w/v) chitosan coating solution containing 1.0% CA (pH 3.3) for 2 min, in 1.0% CA solution (pH 2.6) for 2 min, and in distilled water for 2 min as a control. The treated fruits in each treatment were then packaged in a foam tray, wrapped with 11 μm PVC film and stored at 5°C, 95% RH for 27 days. Pericarp browning, pericarp color, pericarp pH, titratable acidity (TA), weight loss, polyphenol oxidase (PPO) activity, and total phenol were monitored during storage. The results revealed that interaction between chitosan and CA demonstrated the best treatment in postponement of pericarp browning, which was indicated by the lowest browning index and high L* value, chroma, and hue angle. Based on browning index, the fruits treated with citric acid alone and the control fruits were not acceptable after 20 days, which those treated with both CA and chitosan were still acceptable after 27 days of storage. TA had a correlation with the pericarp pH and browning index. Chitosan mixed with citric acid exhibited a higher efficacy in preventing TA degradation in pericarp and maintaining low pericarp pH, compared to 1.0% CA treatment. In addition, low PPO activity and high total phenol content were found when CA was applied in combination with chitosan during storage.